2019
DOI: 10.1016/j.ijmultiphaseflow.2019.103109
|View full text |Cite
|
Sign up to set email alerts
|

Transient stratification force on particles crossing a density interface

Abstract: We perform a series of experiments to measure Lagrangian trajectories of settling and rising particles as they traverse a density interface of thickness ℎ using an index-matched water-saltethanol solution. The experiments confirm the substantial deceleration that particles experience as a result of the additional force exerted on the particle due to the sudden change in density. This stratification force is calculated from the measurement data for all particle trajectories. In absence of suitable parameterisat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…For all radii, however, a jump of velocity occurs when the spheres reach the bottom of the stratified layer. These observations agree with the recent study of Verso et al [14], which relates velocity changes to the crossing of a relatively sharp density interface. In our experiment, the transition is always sharp at the bottom of the stratified layer (see Fig.…”
Section: Dynamics Of the Plastic And Reactive Spheressupporting
confidence: 93%
See 1 more Smart Citation
“…For all radii, however, a jump of velocity occurs when the spheres reach the bottom of the stratified layer. These observations agree with the recent study of Verso et al [14], which relates velocity changes to the crossing of a relatively sharp density interface. In our experiment, the transition is always sharp at the bottom of the stratified layer (see Fig.…”
Section: Dynamics Of the Plastic And Reactive Spheressupporting
confidence: 93%
“…Experimental studies have reported a drag increase for inert particles falling through a sharp density gradient [9][10][11][12][13][14]. In a linearly stratified fluid, Yick et al [15] showed that the drag coefficient can be enhanced by a factor 3 compared to the one in a homogeneous fluid for small Reynolds number (Re = 2aU ν with U the falling velocity, a the sphere radius and ν the fluid kinematic viscosity).…”
Section: Introductionmentioning
confidence: 99%
“…The second parameter is the relative thickness of the fluid density transition layer h 2a which is characterized by the ratio of the layer thickness h to the particle diameter 2a. Several studies have explored gravitational particle settling in sharply stratified fluids [24,27] but reported no bounce phenomenon. In those studies the parameter, h 2a 1, takes value 30 and 10 respectively, whereas in the work of Abaid et al this parameter was much smaller, taking value less than 2.…”
Section: Introductionmentioning
confidence: 99%